Metabolic syndrome in psoriatic arthritis patients: A cross‐sectional study. (20th June 2013) - Sharma, Aman; Gopalakrishnan, Dharmesh; Kumar, Ramesh; Vijayvergiya, Rajesh; Dogra, Sunil
Abstract: Objectives: The major objective of our study was to assess the prevalence of metabolic syndrome in Indian patients with psoriatic arthritis. Method: This was a one‐time survey involving no follow‐up. The study was performed among outpatients attending the speciality clinics of an institutional tertiary referral centre. A consecutive sample of 100 patients diagnosed as having psoriatic arthritis in our clinics was included in the study. Height, weight, body mass index, blood pressure and waist circumference of patients were measured at the enrolment visit. Venous samples were taken after 8 h of overnight fasting for the estimation of serum cholesterol, triglycerides and plasma glucose levels. The primary study outcome was the prevalence of metabolic syndrome in the study population. Results: Fifty‐eight and 59 patients had metabolic syndrome according to the Adult Treatment Panel III criteria and the consensus definition of metabolic syndrome for adult Asian patients, respectively. Patients with metabolic syndrome were older ( P  <   0.001), with longer duration of psoriasis ( P  =   0.017), and higher Bath Ankylosing Spondylitis Activity Index ( P  =   0.016) than those without metabolic syndrome. Conclusions: Metabolic syndrome is common in Asian Indian patients with psoriatic arthritis, especially in those with long‐standing psoriasis and active joint disease.